A Comparative Analysis of Monotheism in Islam and Judaism - Khan, Awais ud Din; Wan Ahmad Fauzi, Wan Husain (NUN Gemilang ENT., 2025)
Monotheism is the belief in a single, all-powerful God. It is a central tenet of both Islam and Judaism. Despite emerging in different historical and cultural contexts, these two Abrahamic faiths share fundamental theological principles while maintaining distinct religious traditions. This article critically examines the concept of monotheism as articulated in Islamic and Jewish scriptures, focusing on the unity of God, His attributes, and His relationship with humanity. It further explores the religious rationales, historical developments, and philosophical influences that have shaped each tradition's understanding of divine oneness. Employing a qualitative doctrinal methodology, the study analyses scriptural texts, theological interpretations, and expert commentaries to reveal both the shared foundations and unique expressions of monotheism in Islam and Judaism. By highlighting these parallels and divergences, the article will contribute to interfaith understanding and foster a deeper appreciation of the theological richness inherent in both traditions.